RESPONS PENAWARAN UBI KAYU DI DAERAH ISTIMEWA YOGYAKARTA - , MIMIN LELANIE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims at (1) knowing the development of the production of cassava (2) knowing the production response of cassava through extensive response approach productivity response (3) knowing the elasticity of cassava production in the short and long term. This study uses secondary data with time series starts in 1982-2011, which was obtained from the Central Bureau of Statistics. Analysis of cassava supply response has been done by using a partial adjustment Nerloveâs model with estimation methods of Ordinary Least Square on E-views 4. The research results showed that (1) the cassava production increased (2) harvested area response was affected by cassava real price, cassava real price last year, sweet potatoes real price, harvested area last year, and the response of productivity has been affected by cassava real price, fertilizers- urea and TSP- real price, precipitation and the productivity last year (3) the offer was responsive to the bidding price, with an elasticity in short term and long term.